Teachers’ Adoption of Emotions-Based Learning Outcomes: Significance of Teachers’ Competence, Creative Performance, and University Performance - Cai, Binbin; Shafait, Zahid; Chen, Lifeng (Frontiers in Psychology, 2022)
Studies have revealed that emotions-based learning outcomes are scarce when teachers’ competence and creative performance are neglected, further university performance in relation with teachers’ emotions-based learning outcomes is disregarded in literature so far. Based on the Attributional theory of achievement motivation and emotion, the purpose of this empirical study is to investigate the effects of Emotional Intelligence (EI) on learning outcomes (social, cognitive, self-growth outcomes and satisfaction with university experience) of academicians in Pakistan higher education institutions (HEIs). This study also examines the mediating role of teacher’s competence (personal assessment) and creative performance (Creative self-efficacy and leadership/supervisor support) in a relationship among EI and learning outcomes. Furthermore, this study ascertained the relationship between learning outcomes and organizational performance (OP) of HEIs. This study used a sample frame of 237 academic professional from Pakistan HEIs, the hypothesized associations were ascertained using partial least squares structural equation modeling method (PLS-SEM). The findings disclose that EI has a positive and significant influence on learning outcomes. Furthermore, an indirect relation between EI and learning outcomes is established through teacher’s competence and creative performance while the relationship between learning outcomes and OP is established also. Results of considered study reinforce the academic understanding of EI and propose how academicians of HEI’s can value their competence and creative performance which in turn enhances learning outcomes and OP. There is a lack of studies in HEIs that investigate the relationship of EI, teacher’s competence, creative performance, learning outcomes and OP. This is one of the initial researches that not only empirically examine the interface of EI, learning outcomes and OP of HEIs’ academicians but also enlighten comprehensions into the prevailing literature by immediate investigation of the mediating role of teacher’s competence and creative performance in fundamental association.